Highly Directive Array Pattern Synthesis in Different phi Planes of a Large CCRAA Using Array Thinning Technique - S. K. Dubey; D. Mandal; A. K. Mishra (Advanced Electromagnetics, 2022)
This paper presents a pattern synthesis method of a sizeable concentric circular ring array (CCRAA) of isotropic antennas using Evolutionary Algorithms. In this method, the array is thinned using the optimum set of binary excitations to achieve the desired highly directive pencil beam patterns with lower peak side lobe level(SLL). The half-power beam width and first null beam width is kept constant to obtain such highly directive beam patterns with lower peak SLL. This pattern is not synthesized to a particular azimuth plane rather in four different ' planes from entire azimuth planes. The isotropic elements are uniformly spaced in the concentric ring. The achieved set of optimum amplitudes are constructed with either 1 or 0 using Differential Evolutionary Algorithm(DE), Genetic Algorithm (GA), and Particle Swarm Optimization Algorithm (PSO). These excitations show the state of the elements. The elements are in “ON” state or in “OFF” state depending upon the excitation ‘1’ or ‘0’. It is also helpful to reduce the complexity of the feed networks. The excitations are also verified in the whole range (0o <phi<360o) of ' planes by selecting four phi planes arbitrarily. The outcomes established the superiority of GA and DE over PSO and also the effectiveness of the proposed method.